Social representations of human rights and political culture in grassroots social organizations - Fernández Fonseca, Edgar (2023)
This article presents the results of a research aimed at characterizing social representations on human rights and political culture in 12 grassroots social organizations in Ciudad Bolivar, Bogota, Colombia. The constitutive trajectories of social organizations converge with the mobilizations oriented to the vindication and demand of rights in the social history of Latin American peripheries, showing the linkage between these, collective action, and the construction of political subjectivity. Knowledge, values, and attitudes are established on them, which influence the network of representations that make possible the organization and understanding of the social world. A qualitative methodology is used with an interpretative approach typical of the social sciences, based on the processual analysis model and through the use of characterization sheets, focus groups and semi-structured interviews. The results allow us to affirm that the figurative core of representation revolves around the triad: life, territory, and participation. The circulation of this triad increases the objects of social appropriation of human rights, by favoring social and cultural processes that broaden its comprehensive margin, through the establishment of cognitive, affective and value patterns oriented towards the political system, where instituting praxis that dislocate the established social order burst in.